Health Tourısm In Turkey And Practıcal Example Of Its Economıc Dımensıons, - Korkmaz, M., Aytaç, A., Yücel, A. S., Kılıç, B., Toker, F., Gümüş, S., (My University, 2014)
Turkey has made significant progress in health tourism within the last 20 years and began to compete with the most successful countries in health tourism. Also, the income obtained from health tourism has an important impact on the income obtained in health sector in Turkey and makes great contribution to the economy. This study aims to investigate the place of health tourism in health sector and its impacts on it. Within this context, various statistical data regarding the spending on health and health tourism between 2004-2013 was used. The data obtain from TUIK (Turkish Statistical Institute) was analysed via PASW Statistics 18 (SPSS-Statistical Package for Social Sciences) package program. Within the scope of the analysis, frequency tables and regression tests were used. The research findings illustrated that private hospitals were preferred more in health tourism, Germany, Bulgaria and Iraq are among the countries that send most health tourists, service is obtained more in other branches and eye and oncology fields and health tourism income is affected by the number of the tourists. The results of the study indicated that foreigners make up 70% of total health tourists in 2013, the rate of health spending in health tourism is 2.3% and health tourism income increased total heath income significantly.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Tourism; Economy; Health Care; Process; World; Competition; Industry